2010
DOI: 10.1517/14656566.2010.484020
|View full text |Cite
|
Sign up to set email alerts
|

Beating the clock: reducing cardiovascular risk by rapid blood pressure reduction with olmesartan

Abstract: In addition to controlling BP, speed of onset of action is an important factor in the management of hypertensive patients and treatments that lower BP rapidly should help to reduce cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…7 The dose used in the current study, 40 mg per day, was higher than that used in many other studies. Is there anything different about olmesartan?…”
mentioning
confidence: 72%
“…7 The dose used in the current study, 40 mg per day, was higher than that used in many other studies. Is there anything different about olmesartan?…”
mentioning
confidence: 72%
“…This is important, since the early achievement of BP control has been associated with better outcomes. [61] These and other studies [47,48] have shown that there are no significant differences in the magnitude of BP reduction with aliskiren according to sex or age, or the presence of metabolic syndrome or obesity.…”
Section: Aliskiren Versus Placebomentioning
confidence: 84%